Relationship Between Prognostic Nutritional Index and Mortality in Overweight or Obese Patients with Cancer: A Multicenter Observational Study - Zhang X; Li JH; Zhang Q; Li QQ; Zhang KP; Tang M; Ge YZ; Li W; Xu HX; Guo ZQ; Shi HP (Dove Medical Press, 2021)
Xi Zhang,1- 3 Jing-Hua Li,4 Qi Zhang,1,3 Qin-Qin Li,1,3 Kang-Ping Zhang,1,3 Meng Tang,1,3 Yi-Zhong Ge,1,3 Wei Li,5 Hong-Xia Xu,6 Zeng-Qing Guo,7 Han-Ping Shi1,3 1Department of Gastrointestinal Surgery/Department of Clinical Nutrition, Beijing Shijitan Hospital, Capital Medical University, Beijing, 100038, People's Republic of China; 2Department of Radiotherapy, Affiliated Hospital of Hebei University, Baoding, 071000, People's Republic of China; 3Beijing International Science and Technology Cooperation Base for Cancer Metabolism and Nutrition, Beijing, 100038, People's Republic of China; 4Department of Hepatobiliary Surgery, Affiliated Hospital of Hebei University, Baoding, 071000, People's Republic of China; 5Cancer Center of the First Hospital of Jilin University, Changchun, 130021, People's Republic of China; 6Department of Clinical Nutrition, Daping Hospital, Third Military Medical University (Army Medical University), Chongqing, 400042, People's Republic of China; 7Department of Medical Oncology, Fujian Cancer Hospital, Fujian Medical University, Fujian, 350014, People's Republic of ChinaCorrespondence: Han-Ping ShiDepartment of Gastrointestinal Surgery/Department of Clinical Nutrition, Beijing Shijitan Hospital, Capital Medical University, Beijing, 100038, People's Republic of ChinaTel +86-10-6392 6985Fax +86-10-6392 6325Email shihp@ccmu.edu.cnBackground: Overweight and obese patients with cancer present with chronic inflammation, dysfunctional antitumor immunity and malnutrition risk. Prognostic nutritional index (PNI) is a promising indicator for predicting inflammatory, immunological and nutritional states; however, its prognostic value in overweight and obese patients with cancer has not been explored. Therefore, the aim of the current study was to explore the prognostic value of PNI levels in overweight and obese patients with cancer.Methods: The current large-scale retrospective cohort multicenter study included 3532 patients. Time-dependent receiver operating characteristic (ROC) curve analysis was used to determine the prediction accuracy of PNI levels for mortality of overweight and obese patients with cancer. Restricted cubic splines were used to model the association between PNI levels and mortality. Association between low PNI and overall survival rate was analyzed using the Kaplan-Meier method and Cox regression model.Results: Area under the curve (AUC) of the PNI for all-cause mortality was higher compared with that of the neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in overweight and obese patients with cancer. There was a significant inverse relationship between PNI levels and all-cause mortality (per SD increment-HR: 0.79; 95% CI: 0.74, 0.85; P< 0.001). Subgroup analysis showed that the risk for mortality significantly decreased with increase in PNI levels in patients at risk of malnutrition (per SD increment-HR: 0.67; 95% CI: 0.57, 0.78; P< 0.001) and elderly patients (per SD increment-HR: 0.74; 95% CI: 0.64, 0.84; P< 0.001). In addition, PNI levels showed an inverse association with mortality in patients without malnutrition risk (per SD increment-HR: 0.81; 95% CI: 0.75, 0.88; P< 0.001). Subgroup analysis based on tumor type showed that low PNI was an independent predictor of poor prognosis for patients with lung cancer, gastric cancer and hepatobiliary and pancreatic cancer.Conclusion: Low PNI levels are associated with an increased risk for all-cause mortality. PNI level is a potential effective inflammation-based prognostic tool for overweight and obese patients with cancer.Keywords: PNI, mortality, overweight or obese, prognosis, cancer patients